Analisis Yuridis Kewenangan Dewan Komisaris Dalam Pelaksanaan Rapat Umum Pemegang Saham (RUPS) - Bagus Firman Wibowo; Sunarmi Sunarmi; Suhaidi Suhaidi; Mahmul Siregar (Universitas Sumatera Utara, 2019)
Abstract. The Board of Commissioners is a PT organ that serves to oversee the tasks carried out by the Board of Directors and also give advice to the Board of Directors, besides that the Board of Commissioners is the company organ in charge of overseeing the Board of Directors in terms of the implementation of GMS. The situation of the Board of Commissioners can hold a GMS, if the Board of Directors is unable or there are other provisions that cause the GMS to not be held, the Board of Commissioners appointed by the shareholders has the authority to hold a GMS. Research This thesis is a normative juridical study accompanied by a legislative approach, this research is also descriptive analytical, the source of data in this study is Law No. 40 of 2007, books, legal dictionaries, journals, decision No. 54 / Pdt.P / 2016 / PN / Plk and 157 / G / 2014 / PTUN.JKT. Data collection techniques in this study are secondary data. Qualitative analysis is research on descriptive research and tends to use analysis. Basically those who function and have the authority to hold the annual GMS and Extraordinary GMS are Directors. Unless the directors are unable or there is a conflict of interest between the directors and the company, the summons is made by the Board of Commissioners. In Article 79 paragraph (1). The implementation of the GMS is entirely an initiative of the Board of Directors. The Board of Commissioners must call the GMS no later than 15 (fifteen) days from the date the request for the implementation of the GMS is received. Furthermore, the GMS convened by the Board of Commissioners based on the GMS call upon the request for the holding of shareholders, only discussed issues relating to the reasons stated in the request letter. Whereas if those who hold a Board of Commissioners are at the request of the shareholders, they are only limited to discussing mass issues relating to the reasons stated in the request letter. The Board of Commissioners has the authority to Organize the GMS in the condition that the Board of Directors does not hold an annual GMS or extraordinary GMS. According to Article 79 paragraph (2) the Board of Commissioners must conduct a GMS if the Board of Directors does not implement the GMS, if the Board of Commissioners does not conduct a GMS, the position of the Board of Commissioners can be dismissed by the shareholders in an LB GMS which will then be held by the shareholders with court approval country. This is included in the Responsibility section due to negligence tort liability, based on the concept of fault relating to interminglend. Keywords : board of commissioners, general meeting of shareholders